REVITALISASI PASAR RAKYAT DAN BAZAR SEBAGAI PILAR EKONOMI KOMUNITAS: STUDI TENTANG DINAMIKA SOSIAL DAN DAYA TAHAN EKONOMI LOKAL DI ERA MODERN - Susanto, Deni; Suwarno, Panji; Suwito, Suwito (Yayasan Sembilan Pemuda Indonesia, 2025)
Traditional markets and bazaars are not merely spaces for economic transactions; they also serve as cultural, social, and identity hubs for local communities. Amidst the dominance of modern retail and the rise of digital economies, the continued existence of traditional markets highlights their resilience and relevance in supporting community welfare. This study aims to explore the role of traditional markets and bazaars as pillars of community-based economies through a qualitative-descriptive approach. Data were collected from academic literature, policy reports, and case studies from various regions in Indonesia. The findings reveal that traditional markets contribute significantly to informal employment, local price stability, and the strengthening of socio-economic networks. Therefore, inclusive, participatory, and sustainable policy support is essential to ensure the continuity of traditional markets as the vanguard of a people-centered economy.